The Close Linkage between Nutrition and Environment through Biodiversity and Sustainability: Local Foods, Traditional Recipes and Sustainable Diets - Durazzo, Alessandra (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
The Close Linkage between Nutrition and Environment through Biodiversity and Sustainability: Local Foods, Traditional Recipes, and Sustainable Diets" is focused on the close correlation between the potential benefits and "functional role" of food and territory, and it includes papers on the characterization of local foods and traditional recipes as well as on the promotion of traditional dietary patterns and sustainable diets.